Measurement of Behavioral Emotion Regulation Strategies in Early Childhood: The Early Emotion Regulation Behavior Questionnaire (EERBQ) - Nicole B. Perry; Jessica M. Dollar (MDPI AG, 2021)
The Early Emotion Regulation Behavior Questionnaire (EERBQ) assesses children's emotion regulation (ER) behavioral strategies in both positive and negative emotional contexts. Psychometric properties and factor structure were tested in a sample of caregivers across the United States (N = 362) with children ages 2-6 years-old (56% male; 73% White). Findings suggest that the EERBQ is psychometrically sound and correlates with other well-established measures of children's socioemotional functioning. Previously, researchers have only been able to assess children's emotional behavioral regulatory strategies in a laboratory setting. Thus, use of the EERBQ addresses a critical gap in the current literature by providing researchers and practitioners with an instrument to measure young children's early emotional functioning outside of a laboratory context. This is particularly salient because early difficulty regulating emotions is often a precursor to persistent adverse developmental outcomes. Thus, the ability to easily to collect rich and predictive behavioral regulation data is imperative for early identification and treatment of youths' emotional and behavioral problems.